Estimation of the degree of surgical difficulty anticipated for pancreatoduodenectomy: Preoperative and intraoperative factors. (26th October 2021) - Kosaka, Hisashi; Satoi, Sohei; Kono, Yumiko; Yamamoto, Tomohisa; Hirooka, Satoshi; Yamaki, So; Hashimoto, Daisuke; Sakaguchi, Tatsuma; Sekimoto, Mitsugu
Abstract: Background: Pancreatoduodenectomy (PD) is a technically complex procedure. Preoperative anticipation of the degree of difficulty could contribute to patient safety during trainee surgical education. Methods: We prospectively administered a questionnaire to the chief surgeon after each PD performed between 2016 and 2018 at our institution (99 consecutive patients). The surgeon rated the difficulty of the procedure; we then analyzed this information against perioperative data. Results: The difficulty of PD was ranked as simple (29.3%), moderate (40.4%), or difficult (30.3%). The difficult procedures required an operative time of 2 h longer than the simple procedures and involved an additional 800 mL of intraoperative blood loss. Postoperative complications were similar in all groups. Multivariate analysis revealed that an unrecognized tissue plane for dissection was an independent determinant of a difficult PD (odds ratio [OR]: 89.2, 95% confidence interval [CI]: 9.2‐861.2; P < .001). Independent predictors of a difficult PD were a pretreatment status of borderline resectable or unresectable (OR: 21.9, CI: 5.3‐90.6; P < .001) and cholangitis during the preoperative period (OR: 4.1, CI: 1.3‐13.0; P = .017). Conclusions: Surgeons deem the PD procedure to be difficult when the proper tissue plane for dissection is unrecognized. Preoperative assessment of the anticipated difficulty could contribute to better operative management. Abstract : A postoperative surgeon questionnaire revealed that an unrecognized tissue plane for dissection was an independent determinant of a difficult pancreatoduodenectomy, while independent predictors were a pretreatment borderline resectable or unresectable status and preoperative cholangitis. Kosaka et al. concluded that preoperative assessment of the anticipated difficulty could contribute to better operative management.